Severe recurrent nocturnal hypoglycemia during chemotherapy with 6-mercaptopurine in a child with acute lymphoblastic leukemia - Eun Mi Cho; Jung Eun Moon; Soo Jung Lee; Cheol Woo Ko (Korean Society of Pediatric Endocrinology, 2018)
Various endocrine dysfunctions occur during chemotherapy, including hypoglycemia. However, reports of hypoglycemia associated with 6-mercaptopurine (6-MP) are rare. Herein, we report an 8-year-old boy with severe symptomatic hypoglycemia likely due to 6-MP during chemotherapy. He had been diagnosed with acute lymphoblastic leukemia 3 years previously and was in the maintenance chemotherapy period. Treatment included oral dexamethasone, methotrexate, and 6-MP, of which only 6-MP was administered daily. Hypoglycemic symptoms appeared mainly at dawn, and his serum glucose dropped to a minimum of 37 mg/dL. Laboratory findings showed nothing specific other than increased serum cortisol, free fatty acids, ketone, alanine aminotransferase, and aspartate aminotransferase. Under the hypothesis of hypoglycemia due to chemotherapy drugs, we changed the time of 6-MP from evening to morning and recommended him to ingest carbohydrate-rich foods before bedtime. Hypoglycemia improved dramatically, and there was no further episode during the remaining maintenance chemotherapy period. To the best of our knowledge, this is the first report of this type of hypoglycemia occurring in an Asian child including Korean.